2021
DOI: 10.3390/app11136148
|View full text |Cite
|
Sign up to set email alerts
|

Modulus of Elasticity for Grain-Supported Carbonates—Determination and Estimation for Preliminary Engineering Purposes

Abstract: The determination and estimation of elastic behaviour are essential in engineering practise, especially in quarrying, mining, construction, and all engineering professions that perform operations dealing with rock materials. Young’s modulus, or modulus of elasticity, is the most important property describing the deformability of rock material. In this paper, grain-supported carbonates from Croatia are described and their elastic modulus and significant physical and mechanical properties are determined. The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Also, the estimation of the modulus of elasticity. The results of their studies showed that petrographic characteristics are very important and directly affect the physical and mechanical properties and the modulus of elasticity (Briševac et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the estimation of the modulus of elasticity. The results of their studies showed that petrographic characteristics are very important and directly affect the physical and mechanical properties and the modulus of elasticity (Briševac et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The research conducted by Donat et al (1964) on slate rocks is one example of the studies conducted around the discussion of anisotropy; Also, Gray (1967), Otto Sanford (1974, studied the anisotropy of phyllite and schist rocks. Studies conducted by Briševac et al (2021) showed that Regression tree models, while using parameters of uniaxial compressive strength and point load index, make it easy to estimate the modulus of elasticity (Homand et al, 1993;Kwaśniewski, 2006 One method to investigate the effect of layering in rock samples is to perform laboratory tests (triaxial compressive strength, uniaxial and Brazilian tensile test) which are performed on the rocks in different directions. Also, one of the tools for analyzing anisotropy and investigating its effect on the mechanical properties of rock is the use of numerical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have used simple and complex methods to create models to estimat the physical and mechanical properties of stone [56][57][58][59][60]. Simple models are based on dia grams and simple regression equations, while complex models are known as multiple re gression equations, neural networks, fuzzy logic models, regression trees, etc.…”
Section: Modelling Methodologymentioning
confidence: 99%
“…Several novel methodologies based on machine learning techniques are available in the literature to determine a rock's elastic constants. For instance, in [35], the authors proposed a comprehensive study of regression models to determine rock samples' elastic properties, which could be adequate when many samples are available. However, due to the challenging drilling environment of the Vaca Muerta formation, recovering a core involves high drilling costs and logistics planning.…”
Section: Experimental Evidence Of Shear-enhanced Compaction In Vaca M...mentioning
confidence: 99%